2014
DOI: 10.1007/s00417-014-2757-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure elevation and post-DMEK glaucoma following Descemet membrane endothelial keratoplasty

Abstract: Incidence of IOP elevation and post-keratoplasty glaucoma after DMEK were low, but regular IOP measurements, especially in eyes with pre-existing glaucoma and bullous keratopathy, are necessary. Steroid-induced IOP elevation was the most frequent reason, and could be treated effectively by tapering down steroid medication or changing the steroid drug. Development of peripheral anterior synechiae after DMEK occured rarely. Therefore, the risk for IOP elevation and especially post-DMEK keratoplasty was reduced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 35 publications
1
44
0
2
Order By: Relevance
“…One study reported an unusually high rate of cystoid macular oedema, detected in up to 13.3% of eyes following DMEK with cataract extraction, and 12.5% of eyes following DMEK alone, within 6 months after surgery 67. Post-DMEK incidence of raised intraocular pressure can be as high as 12% (2.7% developing glaucoma), most of which was secondary to steroid response 68. As a result of improving techniques and reduced detachment rates, primary iatrogenic graft failure rates have also reduced from as high as 20% in initial series to as low as 2.2% 69…”
Section: Complications and Postoperative Managementmentioning
confidence: 99%
“…One study reported an unusually high rate of cystoid macular oedema, detected in up to 13.3% of eyes following DMEK with cataract extraction, and 12.5% of eyes following DMEK alone, within 6 months after surgery 67. Post-DMEK incidence of raised intraocular pressure can be as high as 12% (2.7% developing glaucoma), most of which was secondary to steroid response 68. As a result of improving techniques and reduced detachment rates, primary iatrogenic graft failure rates have also reduced from as high as 20% in initial series to as low as 2.2% 69…”
Section: Complications and Postoperative Managementmentioning
confidence: 99%
“…We reported the postoperative IOP to increase in two (5.12%) cases that were controlled with medical treatment. Maier et al [27] reported IOP increase incidence as 12.1% and glaucoma rate as 2.7% after DMEK.…”
Section: Discussionmentioning
confidence: 97%
“…Ein steroidinduzierter Anstieg des intraokularen Druckes (IOD) wurde in einer Fallserie bei 8 % aller Patienten beobachtet und konnte in al-len Fällen mittels topischer antiglaukomatöser Therapie bzw. Reduktion der Steroidtherapie unter Kontrolle gebracht werden [67]. Generell wird das Risiko nach DMEK für Augendruckanstiege, Glaukominduktionen oder -exazerbationen deutlich niedriger beziffert als nach DS(A)EK oder PKP [67,68].…”
Section: Seltenere Komplikationenunclassified
“…Reduktion der Steroidtherapie unter Kontrolle gebracht werden [67]. Generell wird das Risiko nach DMEK für Augendruckanstiege, Glaukominduktionen oder -exazerbationen deutlich niedriger beziffert als nach DS(A)EK oder PKP [67,68]. Darüber hinaus ist aufgrund der weitaus selteneren immunologischen Abstoßung bei DMEK von einer kumulativ geringeren "Steroidlast" auszugehen als bei den beiden anderen kornealen Transplantationsverfahren.…”
Section: Seltenere Komplikationenunclassified